Education on the Dimensions of Religious Harmony Based on the Strategic Plan of the Ministry of Religion for 2020-2024 for PAK Teachers of Public High Schools in Soe City, TTS Regency: Edukasi Dimensi Kerukunan Umat Beragama Berbasis Rencana Strategis Kementerian Agama Tahun 2020-2024 Bagi Guru PAKSMANegeri Se Kota Soe, Kabupaten TTS - Ali, Umar; Kasse, Simon; Adi Saingo, Yakobus; Yustan Ballo, Jefry (Universitas Lancang Kuning, 2023)
PKM activities with the theme of religious harmony are very relevant and important to implement in the TTS area, especially in the city of Soe because this area has a very high level of religious diversity, so it is still vulnerable to harassment fromirresponsible members of the public with discriminatory actions, intimidation , provocateur issues that are capable of disturbing peace between religious communities. The purpose of the PKM activity is to educate the dimensions of religious harmony based on the ministry of religion's strategic plan for 2020-2024 for PAK teachers at State Senior High Schools in Soe City, TTS Regency. The method used in the PKM activities was Participatory Action Research through interaction with 15 PAK teachers from public high schools in Soe City, TTS Regency, and the data was analyzed reductively which presented the results of the PKM activities by the Study Program Lecturer Team. The Master of PAK-IAKNKupang emphasized to PAK teachers at Public High Schools throughout SoeCity that the application of the values of tolerance, equal rights, and cooperation between religious communities in the world of education, can be a solid foundation for building harmonious relations between religious communities and keeping away from negative behaviors that can divide national unity